Soft Infrastructure in Smart Sustainable Cities: A Literature Review - Ridwan Sutriadi (Pusbindiklatren Bappenas, 2023)
Learning from the cases in Indonesia, the proliferation of advanced technologies has engendered a burgeoning interest in smart city promotion as a dominant developmental theme, and this has an association heavily with physical infrastructure development, while there are other things that need to be thought about. The methodology entails the scholarly works, procurement of data, classification of data, and integration of resultant discoveries. The objective of this article is to furnish a thorough and intricate comprehension of the soft infrastructure that upholds crucial infrastructure systems. Qualitative assessments scrutinize outcomes within multiple frameworks to gauge the efficacy of the supple infrastructure in promoting resilience. As a result, the occurrence of the theme of soft infrastructure in smart sustainable cities poses a novel challenge to continuously enhance their skills and expertise. The soft infrastructure in smart sustainable cities addresses business-spatial, cultural-political, and humane-innovation issues. Such resources can effectively address integrated regional challenges and well-conceived planning for cities.